Amorphous PtNiP particle networks of different particle sizes for the electro-oxidation of hydrazine1. Issue 84 (16th September 2015) - Ma, Yuanyuan; Wang, Hui; Lv, Weizhong; Ji, Shan; Pollet, Bruno G.; Li, Shunxi; Wang, Rongfang
<x xml:space="preserve">Abstract</x> Amorphous PtNiP particle networks with different particle sizes prepared via the reaction temperature control method showed high catalytic activity for hydrazine oxidation compared to the Pt and PtNi catalysts due to its porous, amorphous structure.